Analysis of Contemporary Violin Recordings of 19th Century Repertoire: Identifying Trends and Impacts - Ornoy, Eitan; Cohen, Shai (Frontiers in Psychology, 2018)
The study of violin recordings as evidence of interpretation and performance approach has been quite extensive throughout recent decades. Findings such as the limited use of vibrato in early recordings, the relative stabilization of tempo and rhythm characteristic of mid-20th century violin playing, or the effect of 'historically informed performance' (HIP) on 'mainstream' (MS) violinists performing early music repertoire, are fundamental in the identification of prevailing norms of practice and changes of style that have occurred over time. However, compared to the considerable amount of research conducted on 20th century playing, studies focusing on 21st century violin performances are still quite limited, and are mostly based on recordings of J.S. Bach's sonatas and partitas for solo violin. This paper examines contemporary violin recordings made in recent decades (1999 - 2017). It aims to explore the most current trends in early 21st century violin performance practices and identify the impact of HIP principles on the new generation of players. Unlike most previous research, it focuses on recordings made to 19th century repertoire, thus enlarging the spectrum to include performance analysis of a relatively untouched field and enabling examination of the degree and manner of incorporating 19th century performance attributes (e.g. utilization of rhythmic unevenness, portamento or harmonics) into contemporary praxis. Results suggest an extensive blend of stylistic approaches among currently active violinists, putting into question the relevance of the traditional distinction made between HIP and MS performance styles when it comes to current performance vogue. Incorporating 19th century performance devices while playing 19th century music was traced in varying degrees. Findings are suggested as being part of a general, quasi-postmodern quest for pluralism and elimination of hierarchical classifications, representing an era of 'over-choice' environment.